10 Eye donation in palliative and hospice care settings: patient views and missed opportunities!. (16th November 2022) - Long-Sutehall, Tracy; Bracher, Mike; Madi-Segwagwe, Banyana Cecile; Myall, Michelle; Hurlow, Adam; Faull, Professor Christina; Rayment, Clare; Wale, Jane; Mollart, Sarah; Short, Jill; Lipscombe, Erika; Winstanley, Emma
Abstract : Eye donation in Palliative and Hospice care settings: patient views and missed opportunities. Background: There is a global shortage of donated eye tissue for use in sight saving and sight restoring operations such as corneal transplantation. In the UK the Royal National Institute of Blind People (RNIB) report that over two million people are currently living with sight loss with this figure predicted to rise to approx. four million by 2050. Patients who die in palliative and hospice care settings could potentially donate eye tissue, however, the option of eye donation is not routinely raised in end-of-life planning discussions. Research evidence suggests that health care professionals (HCP) are reluctant to discuss eye donation as they perceive it as something that will distress patients and family members. Aim: This presentation will share findings regarding the views of patients and carers, including: their feelings and thoughts about the option of eye donation being raised with them; who they think should raise this issue; when this option should be discussed and who should be included in the discussion. Findings: Findings are drawn from the NIHR funded national study: Eye Donation from Palliative and Hospice care contexts: investigating Potential, Practice, Preference and Perceptions (EDiPPPP) in partnership with three palliative care and three hospice care settings in England. Findings indicate high potential for eye donation but very low levels of identification of potential donors; low levels of approach to patients and family members about the option of eye donation; lack of inclusion of eye donation in end-of-life care planning and/or clinical meeting discussions (i.e. Multi-Disciplinary Team (MDT) meetings) and very limited awareness raising initiatives or activity to inform patients and carers of the option of eye donation. Conclusion: It is imperative that patients who would want to be a donor are identified and assessed for eligibility for donation as part of high-quality end of life care. It is clear from studies reported over the past 10 years that not a lot has changed regarding the identification, approach, and referral of potential donors from palliative and hospice care settings, and this is due in part to perceptions held by HCPs that patients would be unwilling to engage in discussions regarding the option of eye donation in advance of their death. This perception that is not substantiated by empirical research.